Narrating Conspiracy Theories: A Paradoxical Ethics of Otherness, Propaganda and Mistrust (ENTHYMEMA, 2024)
Reflecting conspiracy theories in contemporary fiction actualises conspiratorial thinking as a specific sociocultural phenomenon and narrative. Four symptomatic novels – George Orwell’s Nineteen Eighty-Four, Ray Bradbury’s Fahrenheit 451, Ahmed Khaled Towfik’s Utopia, and Stephen King’s The Institute – have been analysed from a conspiratorial perspective to illuminate the most efficient ways of shaping the human perception of reality. For this purpose, the following conspiracy elements have been delineated to be the basis of the novels’ poetics: otherness, propaganda, and mistrust. They affect the authors’ strategies of storytelling in the books written in the era of the end of truth. Following an interdisciplinary approach that primarily includes the method of narrative construction and semiotic analysis, the article focuses on the conspiracy elements for plotting the selected novels and explicates conspiracy narratives for manifesting the paradoxical ethics of truth as fiction. Conceptualising this idea in the sociocultural context confers to such a kind of literature a new ethical dimension.
Keywords: Untruthfulness; Troubled Society; Conspiracy Discourse; Fictionality; Escapism